Uncovering the wage differential between formal and informal jobs: Analysis from the Colombian Caribbean Region - Tatiana Cantillo; Victor Cantillo; Victor Cantillo-García; Lucy García (Latin American Economic Review, 2022)
The paper aims to assess the~wage differential that would induce workers to switch between informal and formal sectors, analysing the informal labour market in the Colombian Caribbean region. Relying on the theory of equalising differences, we uncover which workers perceive the highest utility from holding a formal job. Our research sheds light on how workers derive utility from formal and informal job sectors' benefits and to which extent informal workers are willing to accept a lower (or higher) wage to get a job in the formal sector. We also analyse the factors increasing the likelihood to seek employment in the formal sector. Results suggest that, on average, informal workers in the study region are willing to switch to a formal job only if they are offered a salary higher than their current income but are also willing to accept a salary slightly lower than the legal minimum wage in the formal sector. Finally, perceptions of benefits from formal and informal jobs vary with the socio-economic characteristics of individuals, especially by education level and previous work experience.
Keywords: E24; E26; J64; 330; labour informality; Colombian Caribbean region; income; hidden economy